IMPACT OF BEEKEEPING /HONEY HUNTING ON FOREST SPECIES IN THE GUINEA SAVANNAH OF SOUTH EASTERN NIGERIA - C U Okoye (Journal of Agricultural Extension, 2015)
This paper analyses the interactions between traditional beekeeping/honey hunting and the agroforestry/environment in southeastern Nigeria and assess the effects of the former on the later. It attempts, in a rather exploratory manner, to identify the various ways in which inappropriate beekeeping and honey hunting practices result in the loss of important multipurpose agroforestry tree species. Recommendations are proffered towards improving harvesting practices for hive and other non -timber forest products in order to avert the erosion of the natural resource base of fragile farming ecosystems.